Breast Self-Examination Practice and Associated Factors Among Women Attending Family Planning Service in Modjo Public Health Facilities Southwest Ethiopia [Response To Letter] - Asmare Adella G (Dove Medical Press, 2021)
Getachew Asmare Adella Department of Reproductive Health and Nutrition, School of Public Health, College of Health Science and Medicine, Wolaita Sodo University, Wolaita Sodo, EthiopiaCorrespondence: Getachew Asmare Adella Email gasmare35@gmail.com View the original paper by Mrs Urga Workineh and colleagues This is in response to the Letter to the Editor